2014
DOI: 10.1021/ar400203e
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Molecular Oxygen and the Nature of the Active Oxygen Species for CO Oxidation on Oxide Supported Au Catalysts

Abstract: Although highly dispersed Au catalysts with Au nanoparticles (NPs) of a few nanometers in diameter are well-known for their high catalytic activity for several oxidation and reduction reactions already at rather low temperatures for almost 30 years, central aspects of the reaction mechanism are still unresolved. While most studies focused on the active site, the active Au species, and the effect of the support material, the most crucial step during oxidation reactions, the activation of molecular oxygen and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
361
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(393 citation statements)
references
References 39 publications
26
361
1
5
Order By: Relevance
“…5a), as evidenced by the vibration band of linearly adsorbed CO 2 located at 2349 cm −1 . In experiments at higher temperatures CO 2 formation in the Au/TiO 2 system has been explained previously with a Mars-van Krevelen mechanism, in which the oxygen atoms of TiO 2 in close proximity to the gold nanoparticles are used to oxidize CO [3]. The extraction of oxygen from the material, accompanied by the formation of oxygen vacancies, is demonstrated by the vibrational band of CO bound to oxygen vacancies forming at 2140 cm −1 [64].…”
Section: Uhv-ir Spectroscopy Of Au/anatasementioning
confidence: 85%
See 3 more Smart Citations
“…5a), as evidenced by the vibration band of linearly adsorbed CO 2 located at 2349 cm −1 . In experiments at higher temperatures CO 2 formation in the Au/TiO 2 system has been explained previously with a Mars-van Krevelen mechanism, in which the oxygen atoms of TiO 2 in close proximity to the gold nanoparticles are used to oxidize CO [3]. The extraction of oxygen from the material, accompanied by the formation of oxygen vacancies, is demonstrated by the vibrational band of CO bound to oxygen vacancies forming at 2140 cm −1 [64].…”
Section: Uhv-ir Spectroscopy Of Au/anatasementioning
confidence: 85%
“…In this respect, the combination with gold nanoparticles as catalyst or cocatalyst is very common, for example in low temperature CO oxidation [2,3] or for the selective oxidation of alcohols [4][5][6][7]. Since TiO 2 can commonly exist in different crystal structures, with anatase and rutile being the two most common and most studied ones [1], there has been much debate about the (photo)catalytic properties of either of them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface hydroxyl groups on the support are clearly necessary for the most-active catalysts [24][25][26] , and we showed 11 , following work by the Haruta 27,28 , Davis 26,29 , Fujitani 30 and Iglesia 31 groups, that water greatly enhances reaction rates. Several groups also suggested that oxygen vacancies on the support play in important mechanistic role [32][33][34] . More-specific mechanistic PROX investigations by Widmann et al showed that H 2 promotes CO oxidation over Au and the same activated oxygen species is involved in both H 2 and CO oxidation 35 .…”
mentioning
confidence: 99%